Performance of some broiler strains fed varying energy levles in wet season of semi-arid Sokoto, Nigeria - Aliyu, Sa’adu; Bashar, Yahaya A; Abubakar, Aminu; Abdullahi, Aminu U; Ribah, Mohammed Ibrahim; Garba, Sani; Abbas, AY; Mani, AI (Research in Agriculture Livestock and Fisheries, 2018)
Three commercial broiler strains (Arbor-acre, Marshall and Hubbard) were placed under three dietary energy and crude protein levels of 2900 Kcal/kg (ME) - 22% CP, 3100 Kcal/kg (ME) - 23% CP, and 3300 Kcal/kg (ME) - 24% CP as low, medium and high energy levels at starter phase, respectively. At the finisher phase, the birds were fed 2800 Kcal/kg (ME) - 19% CP, 3000 Kcal/kg(ME) - 20% CP and 3200 Kcal/kg (ME) - 21% CP, in order to determine their productive performance in wet season of semi-arid. A total of 675 birds were used in a completely randomized design (CRD) comprising 225 birds each of each strain serving as treatments. Each group was replicated five times so that each replicate had 15 birds. Each strain group was fed three dietary energy levels at both starter and finisher phases for 56 days. Feed and water intakes, mortality, weight gain, feed conversion ratio, Cost/kg gain was determined at the end of the trial. Data recorded for each phase were subjected to Analysis of variance (ANOVA) and least significant difference (LSD) was used to compare the means. Results indicated that Hubbard strain had significantly (P<0.05) lowest cost/kg gain, mortality, feed conversion ratio, feed intake and higher weight gain than other strains. Low energy diet had significant higher (P<0.05) weight gain and lower cost/kg gain than both medium and high energy diets. The study concluded that; Hubbard strain fed low energy diet should be raised in wet season of semi-arid Sokoto due to its lower cost/kg gain, mortality, better feed conversion ratio and higher average daily gain compared to other strains. Res. Agric., Livest. Fish.5(1): 33-42, April 2018